Analyses of organic matter and heavy metal composition in formulated macroalgae-based organic fertilizer. Issue 1 (November 2021) - Widyastuti, S; Jupri, A; Nikmatullah, A; Kurniawan, N S H; Kirana, I A P; Abidin, A S; Hernawan, A; Sunarpi, H; Prasedya, E S
Abstract: The application of inorganic fertilizers has been continuously increasing since last many decades globally. Farmers nowadays heavily rely on the use of inorganic fertilizers to meet the production of their farms and gardens. This becomes a concerning environmentally and also health issue. One solution is to decrease the use of inorganic fertilizers and substitute with organic fertilizers. In our previous work, we have developed macroalgae-based organic fertilizer (MbOF) which show promising results in increasing the growth and yield of various crops and plants. However, the quality of the formulated MbOF has never been accessed. In this study, we analysed the organic matter composition and heavy metal safety profile of the MbOF. Our results show that MbOF contains considerably high organic C (43.05 ± 2.56 %). The cumulative content of total-N (1.91 ± 0.78 %), P2 O5 (2.20 ± 0.81 %) and K2 O (2.18 ± 0.54 %) were also above 4%. Furthermore, the C/N ratio was sufficient (22.54 ± 5.81 %). In addition, heavy metal analyses also show low content of Pb (5.61 ± 0.71 ppm) and Hg (0.29 ± 0.14 ppm). Based on the results, the formulated MbOF could be employed as substitute or used together with inorganic fertilizer to get maximum benefits regarding yield and growth of crops and plants.